Penerapan Kurikulum Merdeka Berbasis Projects Pada Kokurikuler Keagamaan di Madrasah Tsanawiyah Swasta (MTS) Cendikia Medan - Lubis, Parenta (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
This research aims to examine and analyze the implementation of the projects-based independent curriculum in religious co-curricular at the private Tsanawiyah Madrasah (MTS) Cendikia Medan. The purpose of this research is to find out the planning of a project-based independent curriculum in co-curriculars, to find out the application of a project-based independent curriculum in religious co-curriculars, to find out the challenges faced by teachers in implementing the project-based Merdeka learning curriculum in religious co-curriculars. To find out the impact of implementing the project-based Merdeka learning curriculum on religious co-curriculars, to find out how teachers evaluate the achievement of the learning objectives of the project-based Merdeka curriculum on religious co-curriculars, to find out the efforts made in developing the project-based Merdeka learning curriculum on religious co-curriculars. The method used in this research is a qualitative approach, namely systematic analysis to understand in depth an organization or research object. Data collection was carried out using observation, interview and documentation techniques. The results of this research showed that Mts Cendekia had implemented the Independent Curriculum based on religious Co-Curricular, there was an increase in student character, both in terms of morals, responsibility and honesty in students regarding the assignments or projects given. It was found that students had developed in the process and implementation of the projects given, such as keeping the environment and body clean, applying honesty, discipline in worship, and applying Islamic teachings in life.